Impact of diode laser irradiation on the size of Enterococcus faecalis population in the canals of bovine teeth – an in vitro study - Grącka - Mańkowska, Joanna; Zarzycka, Beata; Pawlicka, Halina (Journal of Stomatology, 2015)
Aim of the study. To evaluate the impact of laser diode irradiation on the size of Enterococcus faecalis population in the canals of bovine teeth and to determine the minimum effective diode laser irradiation dose. Material and methods. 1. Freshly extracted single-canal bovine teeth, 2. Enterococcus faecalis strain ATCC 11420 deriving from the Polish Microorganisms Collection of the Institute of Immunology and Experimental Therapy of the Polish Academy of Sciences in Wroclaw, 3. Diode laser (Diode LX mini 980 nm, 10 W, Lasotronix). The prepared and sterilized bovine teeth were infected by E. faecalis, and then incubated in aerobic conditions for 24 hours. The teeth were divided into seven groups (1-7). The laser light was applied for the infected teeth from groups 1-5 in order to determine a narrow range for searching for minimum effective laser irradiation dose. The canals of the teeth from Group 6 were subjected to irrigation with 5.25% NaOCl solution. Group 7 served as an infection control unit. The material gathered from the interior of canals was cultured on the selective Enterococcosel Agar and CFU (Colony Forming Unit) per 1 mg of dentine was determined for each sample. Results. The differences in the obtained average CFU/ mg values for each group were statistically significant (p<0.001). The greatest average CFU/mg value was identified in Group 7 (infection control). The complete eradication of E. faecalis population was observed in Group 6 (5.25% NaOCl). The statistically significant reduction in population was obtained in Group 4 1500 mW, CW – Continuous Wave, laser operating in a continuous wave mode), and the values for Group 3 and 5 (1250 mW – CW and 3000 mW, respectively, laser operating in pulsed mode) were similar. No statistically significant reduction in the size of pathogen population was identified in Group 1 and 2. Conclusions. The conducted laboratory studies prove that diode laser can be a helpful tool in disinfection of root canal infected by Enterococcus faecalis.